Konstruksi Lingkungan Seyyed Hossein Nasr: Studi Kasus: Permukiman Magersari Keraton Kasepuhan dan Keraton Kanoman, Cirebon - Chairunisa Matondang; Ina Helena Agustina (UNISBA Press, 2022)
Abstract. Kasepuahan Village and Keraton Kanoman are located in Lemahwungkuk District, Cirebon City. Keraton Kasepuhan was established in 1430 and Keraton Kanoman was established in 1678, Keraton Kanoman has the main purpose of spreading Islam in the land of Sunda. In Seyyed Hossein Nasr's Environmental Theology there is a relationship between God, Man and Nature that must be maintained for the harmony of human life. So the purpose of this study is to construct Seyyed Hossein Nasr's Environmental Theology and validate how things are going in the Magersari settlement. However, over time, magersari settlements have changed from the shape of buildings to population density which causes settlements to look dense, besides that because of the increasing number of people, the residential environment becomes less maintained and less clean. However, the community still carries out activities such as devotional work, this is done by residents to maintain the cleanliness of their residential environment and they are aware of the importance of maintaining personal and surrounding health. Abstrak. Kelurahan Kasepuahan dan Keraton Kanoman terletak di Kecamatan Lemahwungkuk Kota Cirebon. Keraton Kasepuhan berdiri pada Tahun 1430 dan Keraton Kanoman berdiri pada Tahun 1678, Keraton Kanoman memiliki tujuan utama yaitu untuk menyebarkan agama islam di tanah Sunda. Dalam Teologi Lingkungan Seyyed Hossein Nasr ada nya hubungan Tuhan, Manusia dan Alam yang harus dijaga untuk keharmonisan kehidupan manusia. Maka tujuan dari penelitian ini adalah mengkonstruksikan Teologi Lingkungan Seyyed Hossein Nasr dan memvalidasi bagaimana keadaan di permukiman Magersari. Namun seiring berjalannya waktu, permukiman Magersari mengalami perubahan dari bentuk bangunan hingga kepadatan penduduk yang menyebabkan permukiman terlihat padat, selain itu karena semakin banyak nya masyarakat maka lingkungan permukiman menjadi kurang terjaga dan kurang bersih. Namun masyarakat masih melakukan kegiatan seperti kerja bakti, hal ini dilakukan warga untuk tetap menjaga kebersihan lingkungan permukiman mereka dan mereka sadar akan pentingnya menjaga kesehatan pribadi dan sekitar.